Influence of localized fouling on ballast bed performance: A multiscale investigation with soft-shell contact model - Sen Tian; Longlong Fu; Haonan Xi; Yongjia Qiu; Jiawei Zhang; Shunhua Zhou (Transportation Geotechnics, 2026)

Wetting-induced collapse of loess: Multistage microstructural evolution of particles and pores - Longlong Lv; Yaoxing You; Yukuai Wan; Yingpeng Fu (Transportation Geotechnics, 2026)

Hydroxyl radical bursts triggered by long-term nitrate accumulation accelerate deep soil organic carbon mineralization - Wei Song; Jinzhi Yao; Jindian Liu; Yingdong Fu; Ji Chen; Longlong Xia; Shuping Qin (Journal of Hazardous Materials, 2026)

Validation and applicability analysis of a novel soft-shell contact model for coated granular materials: discrete element modelling and experimental study - Sen Tian; Longlong Fu; Haonan Xi; Yongjia Qiu; Jiawei Zhang; Shunhua Zhou (Computers and Geotechnics, 2026)

Synergistic effects of high temperature and hypoxia on energy metabolism and physiological homeostasis in the Chinese mitten crab (Eriocheir sinensis) - Cong Zhang; Dunqian Deng; Huixia Feng; Su Jiang; Zihao Song; Kai Zhang; Longlong Fu; Shaowu Yin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

New inspirations for efficient water transport in sub-nanopores: The effect of positive charges at the pore entrance - Guangli Liu; Tao Fu; Jinwei Liu; Longlong Wang; Changzhe Zhou; Yi Xu; Huazhang Zhao (Journal of Environmental Chemical Engineering, 2025)

High-flux and stability nanofiltration membranes prepared with β-cyclodextrin and in-situ co-polymerized of TpPa COFs for dye desalination - Changzhe Zhou; Haojie Li; Longlong Wang; Tao Fu; Guangli Liu; Xiaoran Shen; Huazhang Zhao (Journal of Environmental Chemical Engineering, 2025)

Planted Forests in China Have Higher Drought Risk Than Natural Forests - Longlong Ma; Jun Ma; Pu Yan; Feng Tian; Josep Peñuelas; Mukund Palat Rao; Yongshuo Fu; Zhenhong Hu (Global Change Biology, 2025)
To improve the environment and mitigate climate change, China has implemented ambitious projects for natural forest protection and expanded planted forests. However, increased climate variability has led to more frequent and severe droughts, exacerbating the decline of these forests. The drought risk of planted forests is rarely assessed by considering both resistance and resilience, and comparative analyses between natural and planted forests are lacking. Here, we compared drought resistance and resilience in natural and planted forests across China using satellite observations from 2001 to 2020 to understand which forests were at higher risk of drought. The results showed that planted forests exhibited lower drought resistance and resilience compared to natural forests, particularly in subtropical broad‐leaved evergreen forests and warm temperate deciduous broad‐leaved forests. Moreover, drought resistance in planted forests significantly increased, while resilience decreased during 2011–2020 compared to 2001–2010, suggesting a shift in the strategies of planted forests to cope with drought stress. The higher drought risk in planted forests compared to natural forests was mainly attributed to lower forest canopy height and poorer soil nutrients, which limited resistance, and lower canopy height and severe drought characteristics (severity, duration, and frequency), which reduced resilience. These results underscore the higher potential risk of drought exposure in planted forests. To mitigate future drought impacts on planted forests under climate change, enhanced management strategies, including the preservation of natural forests and augmentation of structural diversity in planted forests, are imperative.

The influence of sand content on dynamic behaviors of ballast bed from a multiscale perspective - Shuchen Wang; Longlong Fu; Haonan Xi; Yongjia Qiu; Shunhua Zhou (Transportation Geotechnics, 2024)

Characterizing the regional variation of ballast particles’ movement during the increase of local void in ballast bed - Haonan Xi; Longlong Fu; Shuchen Wang; Yongjia Qiu; Shunhua Zhou; Binglong Wang (Transportation Geotechnics, 2024)

Experimental analysis of sand-bearing muck blockages inside single circle earth pressure balance shield chambers - Chang Ji; Longlong Fu; Shunhua Zhou; Qiyu Yao; Chao He (Tunnelling and Underground Space Technology, 2023)

Integrated miRNA-mRNA transcriptomic analysis of hepatopancreas reveals molecular strategies in Chinese mitten crab (Eriocheir sinensis) under acute nitrite stress - Longlong Fu; Tianheng Gao; Hucheng Jiang; Yan Zhang; Jianlin Pan (Aquaculture International, 2021)

Investigation of a loess-mudstone landslide and the induced structural damage in a high-speed railway tunnel - Shunhua Zhou; Zhiyao Tian; Honggui Di; Peijun Guo; Longlong Fu (Bulletin of Engineering Geology and the Environment, 2020)

Simplified procedure for laterally loaded drilled shafts in spatially random clays - Zhe Luo; Zhongyang Wu; Longlong Fu (Marine Georesources & Geotechnology, 2020)

Staphylococcus aureus causes hepatopancreas browned disease and hepatopancreatic necrosis complications in Chinese mitten crab, Eriocheir sinensis - Longlong Fu; Tianheng Gao; Hucheng Jiang; Faqi Qiang; Yan Zhang; Jianlin Pan (Aquaculture International, 2019)

Effects of Astragalus polysaccharides on antioxidant abilities and non-specific immune responses of Chinese mitten crab, Eriocheir sinensis - Longlong Fu; Gang Zhou; Jianlin Pan; Yuehua Li; Quanping Lu; Jun Zhou; Xuguang Li (Aquaculture International, 2017)

Comparison of growth and pearl production in males and females of the freshwater mussel, Hyriopsis cumingii, in China - Yongchao Zhao; Zhiyi Bai; Longlong Fu; Yue Liu; Guiling Wang; Jiale Li (Aquaculture International, 2013)

Genetic analysis of early growth traits of the triangle shell mussel, Hyriopsis Cumingii, as an insight for potential genetic improvement to pearl quality and yield - Wu Jin; Zhiyi Bai; Longlong Fu; Genfang Zhang; Jiale Li (Aquaculture International, 2012)

Evaluation of laser labeling on growth and survival of the freshwater pearl mussel, Hyriopsis cumingii - Longlong Fu; Zhiyi Bai; Wu Jin; Genfang Zhang; Jiale Li (Aquaculture International, 2012)